Prevention of Contrast Induced Nephropathy by 16-hours Post-contrast Continuous Veno-venous Hemodiafilteration - Al-Bader, Shaikha; El-Reshaid, Kamel (International Journal of Innovative Research in Medical Science, 2019)
Contrast induced nephropathy (CIN) is the most common cause of iatrogenic in-hospital kidney dysfunction with high morbidity and mortality. In our 5-year prospective study, we evaluated the role of 16-hour post-procedural continuous veno-venous hemodiafilteration in a 132 patient with high risk Mehran integer index for CIN who had to be subjected to coronary arteriography including primary one. All patients had eGFR < 40 ml/minute and 23 (17.4%) of whom were < 20%. The results showed stable kidney disease post-contrast with no significant local or systemic complications in both males and females. In-conclusion; we advocate its use to protect high-risk patients from CIN.